Flexural Behavior of Prestressed Steel-Concrete Composite Members with Discontinuous Webs - Jae Yuel Oh; Deuck Hang Lee; Sang Hum Cho; Hyun Kang; Hae-Chang Cho; Kang Su Kim (Advances in Materials Science and Engineering)
The corrugated webbed prestressed (CWPS) composite member was developed to improve the efficiency of the prestress introduced into the steel beam, and experimental studies were performed to examine its structural behavior. Additionally, a unified analysis model that can estimate the nonlinear flexural behavior of the composite member and the accordion effect of the corrugated webbed steel beams at the prestressing stage was proposed. As a consecutive experimental series, in this study, the discontinuous-webbed prestressed (DWPS) composite member was developed, and this innovative composite member can reduce the amount of steel materials used, compared with the former CWPS composite member. Flexural tests were carried out to investigate their structural performances, and their behaviors were analyzed in detail by a nonlinear finite element analysis.